(untitled) (University Journal of Zoology, Rajshahi University, 2010)
Key words: Length-weight relationship; growth condition; Mystus gulio DOI: 10.3329/ujzru.v28i0.5292 Univ. j. zool. Rajshahi Univ. Vol. 28, 2010 pp. 73-75